(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article discusses the linguistic and methodological foundations of teaching grammar in English and Uzbek language learning. Grammar is considered not only as a system of rules, but also as an essential component of communicative competence, language accuracy and meaningful speech production. The article analyzes the role of grammar in foreign and native language education, the relationship between grammatical knowledge and communicative skills, and the methodological principles of teaching grammar effectively. Special attention is paid to the comparison of English and Uzbek grammatical systems, including differences in word order, tense, aspect, voice, articles, cases and sentence structure. The study also examines modern methods of grammar teaching, such as inductive and deductive approaches, contextualized grammar teaching, communicative grammar practice, contrastive analysis and task-based activities. The article concludes that effective grammar teaching should combine linguistic explanation, practical usage, comparison, communication and learner-centered methods.